Distraction Using Virtual Reality Reduces Pain and Anxiety After PCI: Penggunaan Realitas Virtual untuk Mengalihkan Perhatian Mengurangi Nyeri dan Kecemasan Setelah PCI - Shutnan, Ali Hassan Ibrahim; Athbi, Hassan Abdullah (Indonesian Journal on Health Science and Medicine, 2025)
Background: Cardiovascular diseases remain the leading cause of death globally, with percutaneous coronary intervention (PCI) being a common treatment modality. However, post-PCI patients frequently experience significant pain and anxiety. Specific Background: Conventional pain management strategies are often pharmacological and may involve adverse effects, prompting exploration of non-invasive alternatives like virtual reality (VR). Knowledge Gap: Although VR has been explored in various medical contexts, its efficacy in post-PCI recovery remains under-researched. Aims: This randomized clinical trial aimed to evaluate the effect of VR-based distraction on pain and anxiety levels in post-PCI patients. Results: A total of 144 patients were divided equally into intervention and control groups. The VR group, exposed to 3D natural scenes with soothing music, showed significantly lower mean pain (29.60 vs. 57.97) and anxiety scores (2.90 vs. 5.15) than the control group (p < 0.001 for both). Novelty: This study provides robust clinical evidence that immersive VR distraction can be an effective adjunct to standard post-PCI care. Implications: Integrating VR into post-PCI protocols may enhance patient comfort, reduce reliance on medication, and improve recovery experiences without added clinical risk.Highlight : Virtual reality effectively reduces pain and anxiety levels after PCI. There was a significant difference between the intervention and control groups. This distraction technique is non-invasive and easy to apply clinically. Keywords : Virtual Reality, Anxiety, Pain, Percutaneous Coronary Intervention, Distraction Technique